Nilai-nilai Religius dalam Syair Selawat Dulang di Kenagarian Kurai Taji Kecamatan Nan Sabaris Kabupaten Padang Pariaman - Darmawi, Fatimah B.; Gani, Erizal; Chan, Wirsal (Universitas Negeri Padang, 2012)
The purpose of this study is to describe and analyze the religious values ​​contained in the poem salawat platter, which includes Aqidah, Syariah, and Akhlak in Kenagarian Nan Sabaris Kurai Taji district of Padang Pariaman district. The data of this study is religious values ​​in poetry salawat trays. Sources of data in the form of poetry salawat panned Kenagarian Kurai Taji district of Padang Pariaman obtained from the study of personal dokomen through salawat manuscript collection tray of the informants in Kenagarian Nan Sabaris Kurai Taji district of Padang Pariaman district. Data was collected using a descriptive method that focuses on the content analysis, the study of the importance of the assessment content. The findings of the study as a whole poem salawat trays containing religious values ​​of Islam which includes Aqidah, Syariah, and Akhlak.